Electrochemical unzipping of multi-walled carbon nanotubes for facile synthesis of high-quality graphene nanoribbons - Shinde, Dhanraj B.; Debgupta, Joyashish; Kushwaha, Ajay; Aslam, Mohammed; Pillai, Vijayamohanan K. (Journal of the American Chemical Society, 2011)
Here we report a remarkable transformation of carbon nanotubes (CNTs) to nanoribbons composed of a few layers of graphene by a two-step electrochemical approach. This consists of the oxidation of CNTs at controlled potential, followed by reduction to form graphene nanoribbons (GNRs) having smooth edges and fewer defects, as evidenced by multiple characterization techniques, including Raman spectroscopy, atomic force microscopy, and transmission electron microscopy. This type of ``unzipping'' of CNTs (single-walled, multi-walled) in the presence of an interfacial electric field provides unique advantages with respect to the orientation of CNTs, which might make possible the production of GNRs with controlled widths and fewer defects.